Dupilumab reduced impact of severe exacerbations on lung function in patients with moderate‐to‐severe type 2 asthma. Issue 1 (9th August 2022) - Papi, Alberto; Corren, Jonathan; Castro, Mario; Domingo, Christian; Rogers, Linda; Chapman, Kenneth R.; Jackson, Daniel J.; Daizadeh, Nadia; Pandit‐Abid, Nami; Gall, Rebecca; Jacob‐Nara, Juby A.; Rowe, Paul J.; et al.
Abstract: Background: Severe asthma exacerbations increase the risk of accelerated lung function decline. This analysis examined the effect of dupilumab on forced expiratory volume in 1 s (FEV1 ) in patients with moderate‐to‐severe asthma and elevated type 2 biomarkers from phase 3 LIBERTY ASTHMA QUEST (NCT02414854). Methods: Changes from baseline in pre‐ and post‐bronchodilator (BD) FEV1 and 5‐item Asthma Control Questionnaire (ACQ‐5) scores were assessed in patients with elevated type 2 biomarkers at baseline (type 2–150/25: eosinophils ≥150 cells/μl and/or fractional exhaled nitric oxide [FeNO] ≥25 ppb; type 2–300/25: eosinophils ≥300 cells/μl and/or FeNO ≥25 ppb), stratified as exacerbators (≥1 severe exacerbation during the study) or non‐exacerbators. Results: In exacerbators and non‐exacerbators, dupilumab increased pre‐BD FEV1 by Week 2 vs placebo; differences were maintained to Week 52 (type 2–150/25: LS mean difference (LSMD) vs placebo: 0.17 L (95% CI: 0.10–0.24) and 0.17 L (0.12–0.23); type 2–300/25: 0.22 L (0.13–0.30) and 0.21 L (0.15–0.28)), in exacerbators and non‐exacerbators, respectively ( p < .0001). Similar trends were seen for post‐BD FEV1 . Dupilumab vs placebo also showed significantly greater improvements in post‐BD FEV1 0–42 days after first severe exacerbation in type 2–150/25 (LSMD vs placebo: 0.13 L [0.06–0.20]; p = .006) and type 2–300/25 (0.14 L [0.06–0.22]; p = .001) patients. ACQ‐5 improvements were greater with dupilumab vs placebo in both groups. Conclusion: Dupilumab treatment led to improvements in lung function independent of exacerbations and appeared to reduce the impact of exacerbations on lung function in patients who experienced a severe exacerbation during the study. Abstract : This analysis assessed the effect of dupilumab on FEV1 in QUEST patients with moderate‐to‐severe asthma and elevated type 2 biomarkers. Dupilumab significantly increased FEV1, regardless of number of severe exacerbations; FEV1 recovery was more rapid in dupilumab‐ vs placebo‐treated patients. Dupilumab produced rapid and sustained improvement in lung function, including in patients experiencing severe exacerbations.Abbreviations: ACQ‐5, 5‐item Asthma Control Questionnaire; BD, bronchodilator; BL, baseline; FeNO, fractional exhaled nitric oxide; FEV1, forced expiratory volume in 1 second; LS, least squares; q2w, every 2 weeks